Preparation Methods and Applications of CuO-CeO2 Catalysts: A Short Review - Ram Prasad; Gaurav Rattan (Bulletin of Chemical Reaction Engineering & Catalysis, 2010)
The CuO-CeO2 catalytic systems are getting popular for catalyzing very actively the various reactions of environmental, commercial and other importance. In recent years, many methods have been in use for the preparation of versatile CuO-CeO2 catalysts. Reviewing the useful preparation methods of such catalysts is thus the need of the time in view of the globally increasing interest towards all the low temperature redox reactions. This article presents a short review on seventeen different preparation methods of the copperceria catalysts, followed by critical discussions on the related redox properties and advancements accomplished with respect to their application aspect, including a systematic compilation of the concerned newer literature in a well-concievable tabular form. © 2010 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)